Asbabun Nuzul Ayat 158 Surah Al-Baqarah dan Hubungannya dengan Sa’i dalam Haji dan Umroh Bagi Mensyukuri Nikmat (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the asbab al-nuzul of Qur’an Surah Al-Baqarah verse 158 and its relationship with the practice of sa’i in Hajj and Umrah as an expression of gratitude for Allah’s blessings. This verse was revealed to address the doubts of some Companions regarding the legitimacy of sa’i between Safa and Marwah, which during the pre-Islamic era had been associated with idolatrous practices. Using a library research method and exegetical analysis, this study demonstrates that Surah Al-Baqarah verse 158 affirms Safa and Marwah as part of the symbols (sha‘a’ir) of Allah that must be honored and performed within the rites of Hajj and Umrah. The practice of sa’i is not merely a ritual obligation but also embodies profound historical, spiritual, and educational values rooted in the story of Hajar’s struggle in seeking water for Prophet Ismail. Values of patience, effort, reliance on Allah, and gratitude are reflected in every step of sa’i. Understanding the asbab al-nuzul of this verse is expected to encourage Muslims to perform Hajj and Umrah with deeper awareness, sincerity, and meaning, so that worship transcends formal ritual and contributes to character building and the strengthening of faith.